A glyceraldehyde-3-phosphate dehydrogenase pseudogene on the short arm of the human X chromosomes defines a multigene family. - Benham, F J (1984)
A human X chromosome-derived gene sequence which recognises an abundant, 1.2-kb mRNA in several cell types was previously isolated during a study to identify expressed sequences from an X chromosome recombinant library. Further characterisation of this clone, acronym OA1, has shown that it maps to the short arm of the X, at Xp21 to Xp22. A 777-bp fragment of the clone which hybridizes to the 1.2-kb mRNA has been sequenced, and the inferred amino acid sequence shows 80% homology with the published protein sequence for human muscle glyceraldehyde-3-phosphate dehydrogenase (GAPDH). The fragment shows even higher homology (87%) with pig muscle GAPDH. The OA1 clone selects an mRNA which translates in vitro into a polypeptide of 36 K, the subunit size of GAPDH. However, the X-sequence is most probably a pseudogene whose structure is consistent with it having arisen by reverse transcription of a GAPDH or GAPDH-related mRNA followed by insertion into the X chromosome. The GAPDH-related portion of OA1 hybridizes to several DNA fragments in human and mouse DNA, and six fibroblast cDNA clones which cross-hybridize to OA1 identify the same genomic fragments as OA1. This series of clones identifies a new, conserved GAPDH-related multigene family.